Refining Indonesian Language Sound Pronunciation Skills Using InPhA (Indonesian Phonetic Alphabet) - Cicik Tri Jayanti (AL-ISHLAH: Jurnal Pendidikan, 2024)
Interference from regional language pronunciation results in imperfections in pronouncing Indonesian language (IL) sounds. This phenomenon is experienced by students taking the Indonesian Language Phonology course (ILPC), where using IL pronunciation media is needed to enhance personal correction skills. The average scores for consonant, vowel, and diphthong pronunciation phonemes are low. Hence, this research aims to achieve three main objectives: (1) Enhancing students' vowel sound pronunciation skills using InPhA in the ILPC; (2) Enhancing students' consonant sound pronunciation skills using InPhA in the ILPC; and (3) Enhancing students' diphthong sound pronunciation skills using InPhA in the ILPC. This research employs a qualitative research design by implementing Classroom Action Research procedures. The data sources include 67 students from the Indonesian Literature Department, A Public University in Malang, Batch of 2022. The data includes scores for the Assessment of Indonesian Vowel, Consonant, and Diphthong Pronunciation in the pre-cycle, cycle one, and cycle two phases. The research findings indicate that the Average Improvement of Indonesian vowel allophone sound pronunciation consisting of [i], [I], [u], [U], [e], [ɛ], [Ә], [o], [ɔ], and [a] is 35.54%; the Average Improvement of Indonesian consonant sound pronunciation involving 23 consonants namely /p/, /b/, /m/, /f/, /w/, /t/, /n/, /l/, /r/, /ḍ/, /∫/, /s/, /z/, /c/, /j/, /n̴/, /y/, /k/, /g/, /ŋ/, /x/, /h/, and /ʔ/ is 11.5%; and the Average Improvement of Indonesian diphthong sound pronunciation comprising four allophones namely [aI], [ai], [aU], and [oi] is 11.5%. All three aspects demonstrate that using InPhA media can enhance Indonesian vowel, consonant, and diphthong sound pronunciation skills in the ILPC.